Study guides

☆☆

Q: X2 plus 13x plus 36 equals 0?

Write your answer...

Submit

Still have questions?

Related questions

x2 + 13x + 36 = (x + 9)(x + 4)

x2-13x+36=(x-9)(x-4)=0 x=9 or x=4

The factors of x2-13x+36 are 'x-9' and 'x-4'because the expression (x-9)(x-4) can be simplified as x2-13x+36.

(x-4)

x2 + 13x = -30 ∴ x2 + 13x + 30 = 0 ∴ (x + 3)(x + 10) = 0 ∴ x ∈ {-3, -10}

(x + 4)(x + 9)

(x + 9)(x + 4)

42 + x2 = 13x ∴ x2 - 13x + 42 = 0 ∴ (x - 6)(x - 7) = 0 ∴ x ∈ {6, 7}

x2-13x+36 = (x-4)(x-9) when factored

(x-4)(x-9)

x2 + 13x + 12 = (x + 1)(x + 12)

This is a quadratic equation question which will have two answers: 2x2+42 = x2+13x 2x2-x2-13x+42 = 0 x2-13x+42 = 0 Factorising the equation gives you: (x-6)(x-7) = 0 Therefore: x = 6 or x = 7

572 Because 2x11=22 and 13x2=26 and 22x26=572.

2x - 13x + 42 = x +ax + b a + b = 2(x - 6.5x + 21) = 34 = a + b

x2-13x+12 = (x-1)(x-12) when factored

x2 + 36x = 0 x2 = -36x x = -36

if x2 + 7 = 37, then x2 = 29 and x = ±√29

If that's plus 36, it factors to (x - 9)(x - 4) If it's minus 36, it gets ugly in a hurry.

vbh

11+2 = 13 and 2*11 = 22 So: x2+13x+22 = (x+2)(x+11) when factored

It is: (x+1)(x+12) when factored

x2+12x+36=0 2x+12x+36=0 14x+36=0 14x=-36 x=-36/14 x=-2 4/7

(x - 9)(x - 4)

x2 + 13x + 40 = x2 + 5x + 8x + 40 = x(x + 5) + 8(x + 5) = (x + 8)(x + 5)

(x + 10)(x + 3)